Vitamin D-related changes in intracranial volume in older adults: A quantitative neuroimaging study. Issue 3 (March 2015) - Annweiler, Cedric; Bartha, Robert; Goncalves, Sandy; Karras, Spyridon N.; Millet, Pascal; Féron, Francois; Beauchet, Olivier
Highlights Vitamin D is involved in skeletal and brain health. Serum 25OHD concentration was inversely associated with intracranial volume. Serum 25OHD concentration was inversely associated with white matter volume. These findings question the systematization of vitamin D supplementation.